Implementasi Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) sebagai Upaya Peningkatan Mengkonstruksikan Diksi dalam Menulis Karya Ilmiah Siswa di Kota Batam - Yunisa Oktavia; Alpino Susanto; Mhd Johan; Siti Marpuah (Asosiasi Ide Bahasa Kepri, 2025)
This research was conducted at SMA Negeri 4 Batam. This research is based on the students' writing skills that have not been fully trained in writing activities. Even students have limitations in using the right diction. This is because students have less interest in reading so that their absorption in using diction does not support writing activities. Students in doing assignments or exercises to hone their abilities only rely on student worksheets known as LKS. Writing scientific papers that require seriousness and brilliant ideas can apply the cooperative learning model Cooperative Integrated Reading and Composition (CIRC). CIRC is right for improving students' skills in solving problem-solving questions. In the application of CIRC, teacher dominance in learning is reduced. Students are motivated to produce results carefully because they work in groups. Furthermore, students can understand and check each other's work and help weak students. As a result, the CIRC model enhances learning outcomes, particularly in addressing problem-solving tasks. This research employs a qualitative approach through classroom action research. The objective is to enhance the learning process and boost students’ performance in writing scientific papers by utilizing the Cooperative Integrated Reading and Composition (CIRC) strategy. The findings of the study can be summarized as follows: First, the improvement in diction usage when writing scientific papers by students of class XI-IS1 at SMA Negeri 4 Batam was effectively implemented in both Cycle I and Cycle II. Second, the integration of the CIRC model in teaching scientific writing significantly enhanced students’ writing abilities. This progress is reflected in the average scores across the cycles: 58.92 in the pre-cycle, 74.07 in Cycle I, and 83.28 in Cycle II.